Emergency Department Analgesia - Stephen H. Thomas (Cambridge University Press, 2008)
This practical and evidence-based resource for emergency medicine and acute care providers will guide physicians in the selection of an effective therapy, define appropriate dosages to use and, equally important, when a treatment doesn't work, explain why, and what to do next. It opens with chapters on the assessment of pain, the safe and effective provision of analgesia in special populations, and featuring a reference table of drug names and interactions. The coverage moves on to describe the provision of analgesia in the wide range of conditions likely to be encountered in the emergency department. The fundamental strengths of this approach are the comprehensive coverage, focus on practicality, basis in sound evidence, and authorship by specialists with extensive experience based on years of clinical practice